DETERMINANTS OF PROFITABILITY: EVIDENCE FROM POWER AND ENERGY SECTOR - FAREED, Zeeshan; ALI, Zahid; SHAHZAD, Farrukh; NAZIR, Muhammad Imran; ULLAH, Assad (Studia Universitatis Babeș-Bolyai Oeconomica, 2016)
https://doi.org/10.1515/subboec-2016-0005 The study examines the impact of key determinants of profitability of power and energy sector in Pakistan such as firm size, firm age, firm growth, productivity, financial leverage and electricity crisis discussed in the broader inter-disciplinary literature. For this purpose panel data of 16 firms of power and energy sector is taken for 2001 to 2012. The study considers profitability determinants at the firm as well as industry affiliation levels in examining hypotheses developed from resource-based approaches. Random effect model is used to detect the combination of variables that best estimated the impact of the explanatory variables on the dependent variable. The empirical results suggest that firm size, firm growth, and electricity crisis positively impact the profitability. However, firm age, financial leverage and productivity negatively influence the firm profitability. This study also propose that during the electricity crisis the profitability of power sector is increased even production of this sector is very low. The findings further indicate that larger and younger firms with high growth and low productivity are more likely to be profitable. This study has found that firm productivity and firm size are the strongest determinants of profitability in power and energy sector of Pakistan. JEL classification: F65, G23